The Interplay of Banking Development and Legal Reforms - Marbun, Bachtiar; Santoso, Budi; Yunanto, Yunanto (University of Jember, 2024)
The enforcement of mortgage rights plays a pivotal role in ensuring economic stability and protecting citizens' financial interests. Within the broader context of economic governance, the banking sector acts as a fundamental pillar, driving economic growth and safeguarding financial certainty. This study examines the regulatory framework governing the enforcement of mortgage rights in Indonesia, emphasizing its impact on financial security and the reduction of Non-Performing Loans (NPL). Through a normative juridical approach, this research analyzes the existing legal provisions in Indonesia and explores avenues for enhancing the mortgage enforcement process. In addition to legal analysis, philosophical discourse is employed to understand the practical challenges in enforcing mortgage rights. A comparative approach focuses on the Indian legal system, where mortgage rights can be executed without court intervention. India’s approach has effectively reduced Non-Performing Assets (NPA), offering valuable insights into Indonesia’s legal reform efforts. The study suggests adopting a comparable framework in Indonesia could streamline mortgage enforcement procedures, reduce litigation, and enhance financial stability. This research aims to contribute to Indonesia’s broader economic management and governance strategies by proposing legal reforms and promoting a more efficient, competitive, financial security, and equitable financial system.KEYWORDS: Legal Reform, Banking, Morgage Rights, Indonesia, India.